Cybersecurity Leadership in Safeguarding Election Voter Data (Case Study: Implementation of the SIDALIH Information System by the Indonesian General Election Commission) - Khatami, Muhammad Iqbal; Rahayu, Rahayu (JURNAL KOMUNIKASI INDONESIA, 2024)
This research aims to determine the cybersecurity leadership of Indonesia's General Election Commission (KPU RI) in protecting voter data within the Voter Registration Information System (SIDALIH). With the increasing use of information technology in elections, including SIDALIH, these systems have become vulnerable to cyber threats. Previous cyberattacks during Indonesian elections highlight the critical importance of cybersecurity, especially in protecting voters' personal information. Given the growing complexity of cyber threats, organizations need responsive leadership and effective communication governance, with a focus on cybersecurity leadership. The primary research question examines how KPU's cybersecurity leadership ensures voter data security during SIDALIH's deployment in the 2024 elections. The study utilizes Ozkaya's Cybersecurity Leadership framework, comprising five key pillars. The research employs an interpretive paradigm and a qualitative descriptive research design, utilizing a single-case study approach. Findings emphasize the need to prioritize leadership and communication governance, transparency, public awareness, regulatory alignment, robust cybersecurity strategies, interagency collaboration, and adequate resource allocation to enhance voter data security.